Expression of Camelina WRINKLED1 Isoforms Rescue the Seed Phenotype of the Arabidopsis wri1 Mutant and Increase the Triacylglycerol Content in Tobacco Leaves - An, Dahee; Kim, Hyojin; Ju, Seulgi; Go, Young Sam; Kim, Hyun Uk; Suh, Mi Chung (Frontiers in Plant Science, 2017)
Triacylglycerol (TAG) is an energy-rich reserve in plant seeds that is composed of glycerol esters with three fatty acids. Since TAG can be used as a feedstock for the production of biofuels and bio-chemicals, producing TAGs in vegetative tissue is an alternative way of meeting the increasing demand for its usage. The WRINKLED1 (WRI1) gene is a well-established key transcriptional regulator involved in the upregulation of fatty acid biosynthesis in developing seeds. WRI1s from Arabidopsis and several other crops have been previously employed for increasing TAGs in seed and vegetative tissues. In the present study, we first identified three functional CsWRI1 genes (CsWRI1A, B, and C) from the Camelina oil crop and tested their ability to induce TAG synthesis in leaves. The amino acid sequences of CsWRI1s exhibited more than 90% identity with those of Arabidopsis WRI1. The transcript levels of the three CsWRI1 genes showed higher expression levels in developing seeds than in vegetative and floral tissues. When the CsWRI1A, B, or C was introduced into Arabidopsis wri1-3 loss-of-function mutant, the fatty acid content was restored to near wild type levels and percentages of the wrinkled seeds were remarkably reduced in the transgenic lines relative to wri1-3 mutant line. In addition, the fluorescent signals of the enhanced yellow fluorescent protein (eYFP) fused to the CsWRI1 gene were observed in the nuclei of Nicotiana benthamiana leaf epidermal cells. Nile red staining indicated that the transient expression of CsWRI1A, B, or C caused an enhanced accumulation of oil bodies in N. benthamiana leaves. The levels of TAGs was higher by approximately 2.5- to 4.0-fold in N. benthamiana fresh leaves expressing CsWRI1 genes than in the control leaves. These results suggest that the three Camelina WRI1s can be used as key transcriptional regulators to increase fatty acids in biomass.